Association of Good Dairy Farming Practices, Welfare and Performance: A Review (Indian Journal of Animal Production and Management, 2024)
This review underscores the critical role of  good dairy farming practices in enhancing both  animal welfare and dairy performance. International  organizations like the World Organization for  Animal Health (WOAH) and country-specific  protocols emphasize the need for tailored Standard  Operating Procedures (SOPs) to ensure effective  and contextually appropriate practices. Advanced  housing systems for calves, such as pair and group  housing, have shown significant benefits in  improving social interaction, cognitive development,  and overall health. Effective pain management,  particularly during procedures like disbudding, and  optimized feeding strategies, including appropriate  feed delivery timing and frequency, are crucial for  enhancing health and productivity. Proper flooring,  such as rubber mats, significantly improves cow  comfort by providing a softer surface that reduces  the risk of lameness and injuries associated with  concrete floors. Effective pen management helps to  mitigate dominance issues and minimize stress,  leading to better welfare and productivity. Gentle  handling practices, involving positive interactions  like patting and stroking, significantly enhance  animal welfare and milk production compared to  aversive methods. Addressing issues such as mold  and mycotoxins in feed is also essential for  maintaining animal health and avoiding adverse  effects on growth and milk production. Overall,  adopting comprehensive dairy farming practices  that prioritize animal welfare not only improves  health and reduces stress but also leads to  increased dairy productivity and sustainability,  highlighting the interdependence of welfare and  performance in the dairy industry.
Keywords: dairy cattle welfare; handling; housing systems; feeding management; performance